The evolution of speed in athletics: Why the fastest runners are black and swimmers white - Bejan, A.; Jones, E. C.; Charles, J. D. (International Journal of Design & Nature and Ecodynamics, 2010)
Here we explain a much avoided phenomenon in the evolution of speed sports for men and women: The world records in running tend to be set by black athletes and in swimming by white athletes. We show that this phenomenon is predictable from physics. Locomotion is a `falling-forward` cycle, in which body mass falls forward and then rises again. Mass that falls from a higher altitude falls faster, down and forward. In running, the altitude (L1) is set by the position of the center of mass above the ground. In swimming, the altitude is set by the upper body rising above the water, and it is proportional to H - L1, where H is the height of the athlete. The anthropometric literature shows that the center of mass in blacks is 3 percent higher above the ground than in whites. This means that blacks hold a 1.5 percent speed advantage in running, and whites hold a 1.5 percent speed advantage in swimming. Among athletes of the same height Asians are even more favored than whites in swimming but they are not setting records because they are not as tall.